On the Mathematical Modeling of Line-Start Permanent Magnet Synchronous Motors under Static Eccentricity - Ibrahem Hussein; Zakariya Al-Hamouz; M. A. Abido; Abdulaziz Milhem (Energies, 2018)
Line start permanent magnet synchronous motors experience different types of failures, including static eccentricity. The first step in detecting such failures is the mathematical modeling of the motor under healthy and failed conditions. In this paper, an attempt to develop an accurate mathematical model for this motor under static eccentricity is presented. The model is based on the modified winding function method and coupled magnetic circuits approach. The model parameters are calculated directly from the motor winding layout and its geometry. Static eccentricity effects are considered in the motor inductances calculation. The performance of the line start permanent magnet synchronous motor using the developed mathematical model is investigated using MATLAB/SIMULINK® software (2013b, MathWorks, Natick, MA, USA) under healthy and static eccentricity condition for different loading values. A finite element method analysis is conducted to verify the mathematical model results, using the commercial JMAG® software (16.0.02n, JSOL Corporation, Tokyo, Japan). The results show a fine agreement between JMAG® and the developed mathematical model simulation results.